2019
DOI: 10.21037/jtd.2019.07.55
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA-181a-2-3p in cadmium-induced inflammatory responses of human bronchial epithelial cells

Abstract: Background: Inflammation is an important priming event in the pathogenesis of pulmonary diseases, including chronic obstructive pulmonary disease (COPD). Increasing evidence indicates that microRNAs (miRNAs) contribute to the pathogenesis of COPD by regulating inflammatory response. Therefore, it is necessary to investigate novel molecular targets in COPD without any validation in COPD samples in airway inflammation. The aim of our study is to reveal novel miRNAs that can influence molecular targets for COPD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 53 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Among the miRNAs downregulated in severe cases was miR‐181a‐2‐3p, a serum biomarker of chronic obstructive pulmonary disease 31 . Downregulation of miR‐181a‐2‐3p is also associated with enhanced TLR4 and CXCL8 expression 32,33 (Figure 2H).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the miRNAs downregulated in severe cases was miR‐181a‐2‐3p, a serum biomarker of chronic obstructive pulmonary disease 31 . Downregulation of miR‐181a‐2‐3p is also associated with enhanced TLR4 and CXCL8 expression 32,33 (Figure 2H).…”
Section: Resultsmentioning
confidence: 98%
“…Among the miRNAs downregulated in severe cases was miR-181a-2-3p, a serum biomarker of chronic obstructive pulmonary disease. 31 Downregulation of miR-181a-2-3p is also associated with enhanced TLR4 and CXCL8 expression 32,33 (Figure 2H). Another downregulated miRNA was miR-99a-5p targeting the proinflammatory genes, insulin like growth factor 1 receptor (IGF1R) 34,35 and myotubularin-related protein 3 (MTMR3), which were reported to induce weaker antiviral immunity 36,37 ( Figure 2I).…”
Section: Bulk Rna-seq Suggests Biomarker Mirnas As Potential Therapeumentioning
confidence: 95%
“…Global gene expression profiling allowed the identification of miR-181a-2-3p targets involved in Cd-induced inflammatory responses in human bronchial epithelial cells. In particular, the authors demonstrated the involvement of the Toll-like receptor 4 ( TLR4 ), which is a fine sensor influencing inflammatory cascade by stimulation of pro-inflammatory molecules [ 136 , 137 ]. These data evidenced the role of miR-181a-2-3p and its target TLR4 in the regulation of inflammatory response in bronchial cells upon Cd exposure and their potential role in COPD pathophysiology.…”
Section: Air Pollution and Copd: The Role Of Mirnasmentioning
confidence: 99%
“…The results of the present study may provide a promising avenue for treatment of COPD. 19). These participants (no other diseases) did not receive chemotherapy, radiotherapy or other therapy prior to blood collection.…”
Section: Long Non-coding Maternally Expressed Gene 3 Regulates Cigarementioning
confidence: 99%